Strange natives the forgotten memories of a forgetful old woman - Herras, Paolo; Marte, Jerico (Strange natives, 2016)
"Who are strange natives? Actors who become presidents, villains rewritten as heroes, and pre-colonial gods who still walk upon the earth. There are as many strangers, as much as there are natives--But only a few stories are written, while the rest will be forgotten. Among these strange natives is Francis, a spoiled little city, the boy with capiz eyes." -- Provided by publisher